Mechanisms of nocturnal gastroesophageal reflux events in obstructive sleep apnea - Shepherd, K.; Hillman, D.; Holloway, R.; Eastwood, Peter (2011)
Purpose: Obstructive sleep apnea (OSA) is associated with increased nocturnal gastroesophageal reflux (nocturnal GER) events and symptoms. Treatment of OSA with continuous positive airway pressure (CPAP) reduces nocturnal GER in patients with OSA. This study sought to determine the: (1) relationship of nocturnal GER events with apnea/hypopnea and arousal, (2) effect of upper airway obstruction on the barrier function of the lower esophageal sphincter (LES), (3) mechanism of LES failure for each nocturnal GER event and (4) effect of CPAP on LES function during sleep. Methods: Eight patients with OSA and nocturnal GER underwent polysomnography with esophageal manometry and pH monitoring. The first half of the night was spent without CPAP and the second half with 10 cmH 2O CPAP. Results: Baseline LES barrier pressure (P b) was low in these patients. When patients were off CPAP, there were 2.7 ± 1.8 nocturnal GER events per hour and 70 ± 39 obstructive respiratory events per hour. There was no direct relationship between the occurrence of GER and obstructive events. While upper airway obstruction did not alter P b, CPAP tended to increase the nadir P b during LES relaxation (LESR) and decreased the duration of LESR. Conclusions: Upper airway obstructive and nocturnal GER events are not directly related. The relatively low P b in these OSA patients raises the possibility of weakening of the gastroesophageal junction from repetitive strain associated with obstructed breathing events. The favourable effect of CPAP on nocturnal GER is possibly due to an increase in nadir P b and decrease in the duration for which the LES relaxes during swallow-induced and transient LESR. © 2010 Springer-Verlag.